International Cartel Enforcement: Lessons from the 1990s - Simon J. Evenett; Margaret C. Levenstein; Valerie Y. Suslow (University of Massachusetts, Department of Economics, 2001)
The enforcement record of the 1990s has demonstrated that private international cartels are neither relics of the past nor do they always fall quickly under the weight of their own incentive problems. Of a sample of forty such cartels prosecuted by the United States and European Union in the 1990s, twenty-four lasted at least four years. And for the twenty cartels in this sample where sales data are available, the annual worldwide turnover in the affected products exceeded US30billion. Prevailing national competition policies are oriented towards addressing harm done in domestic markets, and in some cases merely prohibit cartels without taking strong enforcement measures. In this paper we propose a series of reforms to national policies and steps to enhance international cooperation that will strengthen the deterrents against international cartelization. Furthermore, aggressive prosecution of cartels must be complemented by vigilance in other areas of competition policy. If not, firms will respond to the enhanced deterrents to cartelization by merging or by taking other measures that lessen competitive pressures.
Keywords: 330